Containing Cefoxitin Costs through a Program to Curtail Use in Surgical Prophylaxis - Geoffrey Taylor; Edith Blondel-Hill; Pamela Kibsey; Erwin Friesen; Ronald Tisdell; Wendy Vaudry (Canadian Journal of Infectious Diseases)
Objective: To reduce drug costs attributable to anti-anaerobic cephalosporins – specifically to reduce cefoxitin use in surgical prophylaxis.